FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Hilda Kamalia, 10.42.02.0128 (Students Journal of Economic and Management, 2013)
The objective of this research is to determine any factors affecting to the stock return. This research uses debt to equity ratio, dividend payout ratio, ownership and liquidity (current ratio) as a proxies of independent variable. Stock return uses actual return from closing price end of December of current year and three days after Income Statement publishing. The samples of the research are listed companies in manufacturing industries that actively trading between 2008-2010 in Indonesian Stock Exchange. The sampling method used is purposive sampling and the results are 45 companies according to the criteria of the sample. The test used are : Regression Analysis. The research finds that debt to equity ratio (DER) dan dividend payout ratio (DPR) have a positive and significant effect to the stock return. The other factors :Ownership and Liquidity do not have any impact to the stock return. In general, itâs discovered that all of the factors have weak influence in explaining stock return variation, which means that stock return mostly determined by other various factors. Keywords : stock return ,debt to equity ratio, dividend payout ratio, ownership,current ratio.